Analysis of the Work Quality of Administrative Employees of Madrasah Aliyah Negeri 2 Medan Model - Layla Nurul Sakinah; Muhammad Irwan Padli Nasution (Journal of Indonesian Management, 2022)
This study aims to determine the quality of work of administrative employees at Madrasah Aliyah Negeri 2 Model Medan. This study uses a qualitative method. The data in this study were obtained through observation, interviews, and documentation. The population of this study consisted of four people, namely the principal, head of administration, administrative staff, and teachers. This study shows that the quality of work carried out by administrative employees is quite good. According to interviews with informants, the business staff of Madrasah Aliyah Negeri 2 Model Medan have self-potential, optimal work results, work procedures, and enthusiasm, but do not yet have a clear and concrete division of tasks so that there are still a number of existing jobs.